Small-field radiotherapy photon beam output evaluation: Detectors reviewed - Lam, S.E.; Bradley, D.A. *; Khandaker, Mayeen Uddin * (Elsevier, 2021)
Small fields (few cm and below) are being applied in therapy independently or as mm/sub-cm segments of larger fields. Included are intensity modulated radiotherapy (IMRT)/volumetric modulated arc therapy (VMAT), proton beam therapy, stereotactic radiosurgery (SRS)/stereotactic radiotherapy (SRT) and stereotactic body radiotherapy (SBRT). With an ability to more closely conform to the target volume, small field applications are nevertheless a challenge to accurate dose evaluation and treatment planning. The influencing factors include finite source size, steep dose gradients, charged particle disequilibrium, detector size and associated volume averaging effects, and changes in energy spectrum and associated dosimetric parameters. Accordingly, small-field dosimetric problems attract interest, not least in consideration of new generation small-volume detectors that promise to reduce energy and dose/dose-rate dependence, also perturbation effects. These include developments made prior to the IAEA-AAPM TRS-483 report on the dosimetry of small static fields in external beam radiotherapy. In present review, the small-field problem is revisited, attention being given to output factor determination using contemporary detectors (Gafchromic film, microDiamond-, diode- and plastic scintillation detectors), also optical fibre dosimeters developed by a University of Surrey/Malaysian Consortium, measurements being made in flattening (FF) and flattening filter-free (FFF) beams. Also included are the effects on output factors in using the daisy-chaining approach associated with the small-field detectors. A survey of small-size dosimeter research shows insignificant difference in small-field output values obtained via direct normalisation or daisy-chaining approach. For fields down to 1 × 1 cm2, microDiamond detector, stereotactic field diode (SFD) and EBT3 film show minor differences (< 3.4%) in the dose response ratio between flattened and non-flattened beams. Present review emphasizes the use of at least two dosimeters to address the variations in small-field dose response using the active micro-dosimeters or passive dosimeters discussed herein.